Tipologi Fotografi Nirmana Dua Dimensi pada Objek Wisata Sejarah Kuningan sebagai Pengembangan Wisata Berkelanjutan - Rika Nugraha; Sigit Setya Kusuma; Yulyanto - (Rekam, 2026)
A Typology of Two-Dimensional Architectural Photography at Historical Tourist Sites in Kuningan as a Means of Developing Sustainable Tourism. This study aims to analyze the application of two-dimensional design photography typology on historical tourism objects in Kuningan Regency as a strategy for developing sustainable tourism. The research employs a qualitative method with a Practice Based Research (PBR) approach, in which photographic practice serves as a means of visual exploration to identify the documentary, aesthetic, and symbolic characteristics of historical sites. The three main objects studied include Situs Makam Van Becks , Gedung Paseban Tri Panca Tunggal and Gedung Perundingan Linggarjati.The analysis shows that the documentary typology of Situs Makam Van Becks presents visual authenticity through the balance of lines, shapes, and natural textures, reflecting the harmony between humans and nature. The aesthetic typology of the Gedung Paseban Tri Panca Tunggal highlights rhythm, color balance, and composition that represent the beauty and wisdom of Sundanese culture. Meanwhile, the symbolic typology of the Gedung Perundingan Linggarjati conveys historical and nationalistic values through simplicity of composition and the sacredness of space. Overall, this study emphasizes that two-dimensional design photography is not merely a medium of documentation but also a tool for cultural interpretation that strengthens local identity and supports the preservation of historical heritage within the framework of sustainable tourism in Kuningan Regency. This study integrates a typology of two-dimensional nirmana-based photography with a Practice-Based Research (PBR) approach as a visual model to support the construction of sustainable tourism imagery based on local culture.